INKULTURASI SEBAGAI USAHA MEWARTAKAN INJIL: KAJIAN EKLESIOLOGIS-HISTORIS PEWARTAAN KEKATOLIKAN DI BALI - Thomas Kadek Lintang Kurniawan; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (STP Reinha Larantuka, 2022)
This paper discusses the inculturative efforts of the missionaries in spreading the gospel in Bali. The missionaries who came to Bali wanted to bring the Catholic faith into people's lives. Inculturative efforts have become a means for missionaries to spread the Gospel in Bali. They tried to make the gospel present in Balinese society as well. The missionaries interacted with the local community and introduced them to the gospel. Through this interaction, the development of the Bible in Bali is still well preserved. This research used historical method. The author traced the history of the inculturation of the Catholic faith in Bali. The results of this research show that this inculturation effort didn’t run smoothly. Many challenges come such as restrictions on reporting, exile, death threats and so on. The missionaries interacted with the local community and introduced the gospel. Through this interaction, the development of the Bible in Bali is still well preserved. It can be seem from architecture of the church building with Balinese cultural nuances, the singing of the inculturation mass in Balinese, the Eucharist in Balinese and so on. Therefore, Catholicism in Bali has survived. Most of the Catholics in Bali still maintain the legacy of the missionaries and try to be grace of the world.